Essays on bank PME finance, banking structures and governance mechanisms in emerginig and less developed economies - Tacneng, Ruth (Université de Limoges, 2013)
The aim of this thesis is to examine several issues that banks confront in emerging and less developed economies such as SME financing and bank governance mechanisms. We first provide an overview of the level of bank SME financing in an economy where banks are mandated by law to lend to SMEs. We find large banks, foreign-owned, and well-managed ones to have low small firm financing exposures. Using a newly-gathered survey data of Philippine banks, we find that all banks perceive the SME market to be profitable. However, banks lend less to SMEs because of their opacity and that lending technologies are largely underdeveloped to serve small firms. Moreover, our results show that credit scoring and factoring are the arms-length lending technologies that are most suited to small firm lending. Examining the impact of income diversification on profitability on Philippine commercial banks, we find smaller banks, foreign banks and banks that lend less to SMEs to derive larger gains from a shift towards non-interest income. Investigating the effects of different governance mechanisms on bank risk taking in an economy where foreign ownership restrictions exist, our results indicate that minority foreign owners have a positive impact on bank performance, particularly, at lower levels of control manifested by dominant domestic shareholders. We also tackle the impact of ownership concentration on bank risk in less developed economies using an institutional approach. The results show that an increase in ownership concentration is associated with higher risk but better quality of institutions mitigates the negative impact of ownership concentration, notably in reducing credit risk. L'objectif de cette thèse est d’examiner les problèmes des banques dans les pays émergents et moins développés, tel que le financement des PME et les mécanismes de gouvernance bancaire. Nous étudions l’état de financement bancaire des PME dans un pays où les banques sont obligées d’allouer une part de leurs prêts aux PME. Nous trouvons que les grandes banques et les banques étrangères allouent moins de crédits aux PME. En utilisant un sondage que nous avons réalisé auprès des banques philippines, nos résultats montrent que le secteur des PME est perçu comme un marché rentable. Les banques sont contraintes à prêter aux petites entreprises à cause de l’opacité de ces PME. Le credit scoring et le factoring sont les techniques de financement les plus adaptées pour financer les petites entreprises. En examinant l’impact de la diversification du revenu sur la rentabilité des banques commerciales, nous trouvons que les banques étrangères et les petites banques bénéficient de l’augmentation des revenus hors intérêts. Nous testons l’impact des actionnaires étrangers minoritaires sur le risque bancaire dans un pays où les actions détenues par les étrangers sont limitées. Nous trouvons que les banques domestiques peuvent diminuer leurs créances douteuses lorsque le droit de vote des actionnaires minoritaires étrangers augmente. L’étude de la structure actionnariale des banques dans les pays moins développés montre qu’une augmentation de la concentration de la structure actionnariale est associée à un niveau de risque plus élevé. Toutefois, de meilleures institutions peuvent atténuer l’impact de la concentration de la structure actionnariale en réduisant le risque de crédit.
Keywords: Banques; Pays en voie de développement; Petites et moyennes entreprises